SLE presenting as parotitis and secondary Sjogren’s syndrome - Mohd Shah, Azarisman Shah; H, Heselynn (Singapore Medical Association, 2007)
A 38-year-old woman presented with rightsided parotid swelling, dry mouth and dry eyes of one year duration. Her Schirmer’s test and sialometry were positive and histopathology showed lymphoplasmacytic infiltration. She al so had concomi tant normochromic , normocytic anaemia and mild haematuria. Her anti-nuclear antibody titre was also positive, 1:640, with a speckled pattern on immunofluorescence. We discuss the atypical presentation of systemic lupus erythematosus, particularly parotitis and secondary Sjogren’s syndrome.